Taking responsibility among football coaches from the perspective of Iraqi Premier League players - Anwar , Ali; khaled, Zeena (Journal of Physical Education, 2023)
A coach who faces difficulty in assuming responsibility tends to stumble or persist in a certain task or a certain way of dealing with the task. Therefore, when a coach undertakes a task, whether in the training process or in competitions, the coach assumes responsibility, which means maturity, meaning that the coach is responsible for His behavior towards the players. The research aims to: build a measure of assuming responsibility for football coaches from the point of view of the Iraqi Premier League players. Knowing the assumption of responsibility for football coaches from the point of view of the Iraqi Premier League players. To achieve the objectives of the research, the researchers chose the descriptive approach using the survey method, and the research sample was chosen randomly and the research samples were distributed. The Iraqi Premier League players are as follows: The sample of the reconnaissance experiment included (30) players, with a percentage of (5.01%) from the research community. They were chosen by a simple random method, drawing lots, and included (150) players, with a percentage of (25.08), and included (100). ) player, with a percentage of (16.72) from the research community. After building the scale based on health scientific foundations, the researchers arrived at a final scale in the hope of applying it and applying it. The results were extracted to conclude the following: that soccer coaches have a commitment to human ethics and care for them on the personal and collective level. That soccer coaches have The ability to analyze scientific information and follow different methods to reach the desired goals based on that information. The researchers also recommended several recommendations, including supporting football coaches by providing material and moral support to encourage them to develop their level of performance, and holding training courses and seminars that raise the level of technical and training coaches.